2005
DOI: 10.1128/iai.73.8.4684-4693.2005
|View full text |Cite
|
Sign up to set email alerts
|

T-Cell-Stimulating Protein A Elicits Immune Responses during Meningococcal Carriage and Human Disease

Abstract: In recognition of the need for immunological memory-inducing components for future Neisseria meningitidis group B vaccines, we previously searched the proteome of N. meningitidis and identified T-cell-stimulating protein A (TspA). This study was designed to confirm the immunogencity of TspA and to examine the subset of T-helper cell responses to the protein in patients and nasopharyngeal carriers. The tspA gene was reconstructed, cloned, and expressed in Escherichia coli, and the recombinant TspA (rTspA) prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 41 publications
0
9
0
Order By: Relevance
“…Independently of CEACAM1, T-cell proliferative responses were also shown to be enhanced by meningococcal lysates or recombinant TspA (31). In studies on N. gonorrhoeae-T-cell interactions, it has been shown that Th1 and Th2 cytokines are upregulated by PBMC upon exposure to N. gonorrhoeae strain F62 (Opa Ϫ Pil ϩ ) (30).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Independently of CEACAM1, T-cell proliferative responses were also shown to be enhanced by meningococcal lysates or recombinant TspA (31). In studies on N. gonorrhoeae-T-cell interactions, it has been shown that Th1 and Th2 cytokines are upregulated by PBMC upon exposure to N. gonorrhoeae strain F62 (Opa Ϫ Pil ϩ ) (30).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, they express Opa proteins that bind to receptors on T cells and could downmodulate their functions. They also express other surface antigens that have been shown to induce T-cell proliferation to various extents (27,31,34,38). However, such antigens may vary between species and strains.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…PCR analysis and nucleotide sequencing confirmed the insertion of the 2 kb cassette into the tspA locus (data not shown). To verify the genetic inactivation of tspA , meningococcal lysates of both the wild type and mutant were analysed by immunoblotting using rabbit TspA‐specific polyclonal antibodies (RαTspA) (Robinson et al ., 2005). As expected, TspA was not detected in the knockout strain, indicating that the mutant was completely deficient in TspA expression.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, TspA is being investigated as a possible T‐cell stimulating component of future meningococcal vaccines (Robinson et al ., 2005). Analysis of the TspA primary structure predicted a number of features including an N‐terminal signal peptide, a hydrophobic transmembrane region, and a repeat region consisting of five 19 aa repeats (ADDLSALLQPXXXPXVEEN), the significance of which is not known, but which might be involved in protein–protein interactions (Robinson et al ., 2005). Furthermore, a strong match was found between a 52 aa region of the N‐terminal region of TspA and the LysM domain (Pfam Accession No.…”
Section: Introductionmentioning
confidence: 99%